2018
DOI: 10.22199/s07187475.2018.0002.00001
|View full text |Cite
|
Sign up to set email alerts
|

Relaciones intrafamiliares y calidad de vida relacionada con la salud en adolescentes mexicanos que se autolesionan sin intención suicida

Abstract: OBJETIVO: determinar la existencia de asociación entre las relaciones intrafamiliares (RI) y la calidad de vida relacionada con la salud (CVRS) en adolescentes mexicanos que se autolesionan. MÉTODO: Diseño observacional y transversal. Participaron 545 adolescentes de ambos sexos, 58.17% mujeres y 14.49 ±1.7 de edad. Se utilizó la versión mexicana del ISSIQ-A, la E.R.I. y el KIDSCREEN-52. Se aplicaron modelos de regresión logística para determinar la asociación de las RI y la CVRS, ajustando por variables contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
6
0
3
Order By: Relevance
“…It is worth noting that, for both young men and women, the difficulties variable not only appeared in the regression models but was also second in relevance. Various findings agree that family conflicts are associated with depression in adolescents (Fosco & Lydon-Staley, 2019;Perales-Blum & Loredo, 2015), while a low perception of difficulties improves the mood and psychological well-being of Mexican adolescents (Chávez-Flores et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…It is worth noting that, for both young men and women, the difficulties variable not only appeared in the regression models but was also second in relevance. Various findings agree that family conflicts are associated with depression in adolescents (Fosco & Lydon-Staley, 2019;Perales-Blum & Loredo, 2015), while a low perception of difficulties improves the mood and psychological well-being of Mexican adolescents (Chávez-Flores et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with this finding, Fosco & Lydon-Staley (2019) argued that family cohesion is negatively related to depression rates. Similarly, Morales Rodríguez and Rivera Alcántar (2012) found a negative correlation between the management of sadness and the union and support perceived by Mexican adolescents, and Chávez-Flores et al (2018) reported that family union and support increased psychological well-being in adolescents in Mexico.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations